Nurturing Children’s Socio-Emotional Development Through a Love-Based Arabic Curriculum: A Psychopedagogical Analysis - Murtadho, Mohamad Aris; Amrullah, Ahmad Fikri; Al Muiz, Mochamad Nasichin (Al Huwiyah: Journal of Woman and Children Studies, 2026)
Early childhood Arabic language instruction often faces methodological challenges that cause learning anxiety, necessitating approaches that prioritize children's socio-emotional well-being. This study explores the implementation of a "love-based curriculum" to create a holistic learning experience. Employing a qualitative descriptive approach through an integrative literature review, this research critically analyzes recent scholarly sources to construct a conceptual framework. The results indicate that a love-based curriculum rooted in affection, empathy, and positive reinforcement and significantly fosters an environment conducive to children's socio-emotional and cognitive development. By integrating psycho pedagogical principles, such as the Zone of Proximal Development (ZPD) and multiple intelligences, teachers can design concrete, stress-free, play-based activities. The study concludes that internalizing humanistic values mitigates language anxiety and strengthens character formation. Practically, this framework equips educators and parents to transform rigid linguistic instruction into an empathetic, child-centered ecosystem.